2020
DOI: 10.1002/ppul.24943
|View full text |Cite
|
Sign up to set email alerts
|

Electronic adherence monitoring identifies severe preschool wheezers who are steroid responsive

Abstract: Little is known about adherence to inhaled corticosteroids (ICS) in preschool children with troublesome wheeze. Children with aeroallergen senitization, or those reporting multiple trigger wheeze (MTW), are more likely to respond to ICS. We hypothesized that adherence to ICS and symptom control are only positively related in atopic children, or those reporting MTW. Patients aged 1 to 5 years with recurrent wheeze prescribed ICS were recruited from a tertiary respiratory clinic. Clinical phenotype and aeroaller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…3 , 4 However, van Boven et al reported that more than 80% of patients (98/120) commencing GINA step 5 therapies for severe asthma had poor adherence to ICS/long-acting beta agonist therapy over the previous 12 months. 61 In a study of preschool-age children with severe wheeze by Bingham et al, 62 50% (24/48) had suboptimal adherence with ICS, while Lee et al 63 reported that at least 50% of 69 patients with difficult asthma eligible for novel therapies, such as biologics and thermoplasty, were nonadherent with their ICS or ICS/long-acting beta agonist therapy medication. These studies highlight an unmet need for better identification of medication adherence in patients with respiratory disease.…”
Section: The Capability To Incorporate Insights On Patient Behavior I...mentioning
confidence: 99%
“…3 , 4 However, van Boven et al reported that more than 80% of patients (98/120) commencing GINA step 5 therapies for severe asthma had poor adherence to ICS/long-acting beta agonist therapy over the previous 12 months. 61 In a study of preschool-age children with severe wheeze by Bingham et al, 62 50% (24/48) had suboptimal adherence with ICS, while Lee et al 63 reported that at least 50% of 69 patients with difficult asthma eligible for novel therapies, such as biologics and thermoplasty, were nonadherent with their ICS or ICS/long-acting beta agonist therapy medication. These studies highlight an unmet need for better identification of medication adherence in patients with respiratory disease.…”
Section: The Capability To Incorporate Insights On Patient Behavior I...mentioning
confidence: 99%